(untitled) (Education in the 21st Century, 2023)
For the correct choice of words in speech, the formation of skills of their use in accordance with the speech situation, the goals in the secondary school program of the Armenian language of the middle classes are both the study of grammatical orders of the verb, and the recognition and differentiation of personal and impersonal forms of the verb (derbay). The targeted comparison of modern teaching methods, the use of appropriate methodological steps can determine the effectiveness of teaching impersonal verbs, making grammatical material understandable not only in terms of semantic, but also formal, syntactic features. The differentiated study of verbs using various interactive methods reveals their role in speech, morphological meaning and syntactic application. The purpose of teaching dependent derbay is not only to recognize and differentiate these forms, but also to understand the changes made by these words in the speech, and to express different relations through them, to develop the ability to correctly use these inclined verb forms in the word, to distinguish erroneous derbay forms.